Pengaruh Gaya Kepemimpinan Transformasional dan Komunikasi Interpersonal terhadap Kinerja Karyawan - Anita Gesti Timur Sari (SMARTINDO, 2023)
A company can achieve its vision and mission with qualified and competent human resources who are honest in acting and are responsible for the work that has become their job description. HR is also meant to include leaders who are in charge of the entire company. One of the existing and influential leadership styles is the transformational leadership style. Besides leadership style, communication also has an important role in coordinating between divisions with one another, including with leaders and/or divisions under them. Communication that runs face to face and/or directly from the sender of the message and the recipient of the message is called interpersonal communication. Knowing the effect of transformational leadership style on employee performance. Leadership style and communication are two things that influence employee performance. The purpose of this study was to determine the effect of transformational leadership style and interpersonal communication on employee performance. The respondents of this study were 100 lecturers and the data collection method was by distributing electronic questionnaires to the lecturers. Data analysis in this study used SEM (Structural Equation Model) program LISREL version 8.70. The results of the analysis and proc essing of research data show that leadership, transactional and authoritarian styles at medical colleges in Central Java have a positive and significant effect on lecturer performance, while transformational and authentic leadership styles have no significant effect on lecturer performance. Another journal explains that the research was conducted at MAN 2 Jalan Willem Iskandar No. 7a Medan from January to March 2019. This research is a quantitative study, the population and sample size are the same, namely 68 people, using the Totally Sampling method. There is a positive and significant effect of interpersonal communication on teacher performance. by 29.3%. There is a positive and significant influence of organizational culture on teacher performance of 71.0%. There is a positive and significant influence of leadership style on teacher performance of 70.9%. There is a positive and significant influence between interpersonal communication, organizational culture, leadership style together on teacher performance by 78.9%.